2022
DOI: 10.3390/suschem3010006
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochloric Acid Leaching of Philippine Coal Fly Ash: Investigation and Optimisation of Leaching Parameters by Response Surface Methodology (RSM)

Abstract: Coal Fly Ash (CFA) is a hazardous waste from coal-fired power plants, but has increasingly become a popular supplementary cementitious material for cement in the construction industry. As a secondary resource of REE, its main advantage lies in its fine particle size that eliminates the need for costly and energy-intensive comminution. In this study, the potential of CFA from the Philippines as a secondary REE resource was investigated by direct leaching of REEs with hydrochloric acid (HCl). The CFA sample came… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Products M n+ (aq) + nA − (aq) + yL (org) M(A) (n) •yL (org) − /(M (hyd) •L (y) (n+1) •nA − ) org (5) Furthermore, it is observed that CMPO and DGA have similar behavior in the extraction of Am(III) [52]. ATR-FTIR analysis of the loaded resin shows that the peaks of C=O and P=O have shifted, indicating that they have coordinated with REEs after the adsorption of Y and Ce.…”
Section: Reactantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Products M n+ (aq) + nA − (aq) + yL (org) M(A) (n) •yL (org) − /(M (hyd) •L (y) (n+1) •nA − ) org (5) Furthermore, it is observed that CMPO and DGA have similar behavior in the extraction of Am(III) [52]. ATR-FTIR analysis of the loaded resin shows that the peaks of C=O and P=O have shifted, indicating that they have coordinated with REEs after the adsorption of Y and Ce.…”
Section: Reactantsmentioning
confidence: 99%
“…The Rare-Earth Elements (REEs), a group of 17 elements exhibiting similar chemical properties, have become vital in the last 30 years for the advancement of renewable energy and clean storage technologies owing to their unique magnetic, phosphorescent, and catalytic properties [1][2][3]. In 3 MW wind turbines, for example, 3 tons of REEs are needed [4], while in electric vehicles (EVs), REEs like neodymium (Nd), praseodymium (Pr), samarium (Sm), and dysprosium (Dy) are used in high efficiency and strong permanent magnets [2,5,6]. In 2012, the demand for Dy and Nd for the next 25 years was projected to increase by at least 700% and 2600%, respectively [7].…”
Section: Introductionmentioning
confidence: 99%
“…The most notorious and widely reported impacts of coal utilization is related to the air. Coal combustion causes serious environmental issues like the generation of fly and bottom ashes containing soluble B and Se, release of particulate matter (PM), and emissions of hazardous pollutants like Hg, As, CO 2 , SO x , and NO x to the air [ [13] , [14] , [15] ]. Boron and Se are essential micronutrients but toxic at high concentrations to animals and humans [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some countries, these ashes are disposed of in special landfills handling hazardous wastes. However, recently, both of fly and bottom ashes were utilized for many purposes in cement industries as well as agriculture [ 14 , 22 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…To technically and economically render global coal ash deposits resourceful for REEs, significant research input in industry and academia on a global basis is essential, and such an initiative will be a stepping stone for greener alternatives to producing REEs , given the environmental pollution associated with conventional mining practices (Zapp et al, 2022;Yin et al, 2021;. Consequently, the scientific literature on the extraction of REEs from coal ash abounds (Seferinoğlu,2003;Dahan, et al, 2022;Prihutami et al, 2021;Pan et al, 2020).While significant breakthrough in research and commercialization of research findings is yet to be realized, intensive research has reported the advantages and shortfalls in light of technical and economic viabilities (Huang et al, 2019;Miranda et al, 2022;Das et al, 2018;Kim et al, 2019). Moreover, the development of suitable chemical and physical extraction process for the extraction of REEs from coal ash draws on knowledge of their occurrence in these ashes.…”
Section: Introductionmentioning
confidence: 99%